Preoperative decision making for renal cell carcinoma: cystic morphology in cross-sectional imaging might predict lower malignant potential - Huber, Johannes; Winkler, Alexandra; Jakobi, Hildegard; Bruckner, Thomas; Roth, Wilfried; Hallscheidt, Peter; Daneshvar, Keivan; Hohenfellner, Markus; Pahernik, Sascha (Urologic oncology, 2014)
Objectives - Several histologic studies showed more favorable oncologic outcome for renal cell carcinoma (RCC) with cystic change. However, there is no prognostic tool to judge on cystic RCC preoperatively. We hypothesized, that cystic morphology in cross-sectional imaging predicts lower malignant potential. - Materials and methods - From our prospectively conducted oncologic database, we identified 825 patients who underwent surgery for malignant renal tumors between 2001 and 2010. In 348 cases (42%), adequate imaging was available for an independent review by 2 radiologists. We excluded recurrent and synchronous bilateral RCC, familial syndromes, collecting duct carcinoma, and metastases of other origin. For the resulting 319 patients, we compared clinical, pathologic, and survival outcomes. - Results - Median age was 63 (19-88) years and 220 (69%) patients were male. Median follow-up was 1.7 (0-9.8) years. Of 319 renal masses, 277 (86.8%) were solid and 42 (13.2%) were cystic. In cystic RCC, median tumor diameter was lower (3cm vs. 4cm, P = 0.002) and nephron-sparing surgery was more frequent (69% vs. 41.5%, P = 0.002). None of the patients with cystic RCC and 56 (20.2%) with solid RCC had synchronous systemic disease (P = 0.001). The nuclear grade of cystic RCC was more favorable (P = 0.002). Patients with cystic RCC showed better overall (P = 0.049) and cancer-specific survival (P = 0.027). In a multivariate model, only synchronous metastases, positive R status, and greater tumor diameter were independent risk factors (P≤ 0.03). - Conclusions - We report the first study to show that cystic morphology in cross-sectional imaging might predict RCC with a lower malignant potential. This insight could allow less invasive treatment strategies in selected patients.
Available online 12 April 2013
Gesehen am 23.10.2020